Genomic insights and functional evaluation of Lacticaseibacillus paracasei EG005: a promising probiotic with enhanced antioxidant activity - Kim, Jisu; Jo, Jinchul; Cho, Seoae; Kim, Heebal (Frontiers in Microbiology, 2024)
Introduction: Probiotics, such as Lacticaseibacillus paracasei EG005, are gaining attention for their health benefits, particularly in reducing oxidative stress. The goal of this study was to reinforce the antioxidant capacity of EG005, along with comprehensive genomic analysis, with a focus on assessing superoxide dismutase (SOD) activity, acid resistance and bile tolerance, and safety. Methods: EG005 was screened for SOD activity and change of SOD activity was tested under various pH conditions. Its survival rates were assessed in acidic (pH 2.5) and bile salt (0.3%) conditions and the antibiotic MIC test and hemolysis test were performed to evaluate safety. Genetic analyses including functional identification and phylogenetic tree construction were performed. The SOD overexpression system was constructed using Ptuf, Pldh1, Plhd2, and Pldh3 strong promoters. Results: EG005 demonstrated higher SOD activity compared to Lacticaseibacillus rhamnosus GG, with optimal activity at pH 7.0. It showed significant acid and bile tolerance, with survival rates recovering to 100% after 3 hours in acidic conditions. Phylogenetic analysis confirmed that EG005 is closely related to other L. paracasei strains with ANI values above 98%. Overexpression of SOD using the Ptuf promoter resulted in a two-fold increase in activity compared to the controls. Additionally, EG005 exhibited no hemolytic activity and showed antibiotic susceptibility within safe limits. Discussion: Our findings highlight EG005's potential as a probiotic with robust antioxidant activity and high tolerance to gastrointestinal conditions. Its unique genetic profile and enhanced SOD activity through strong promoter support its application in probiotic therapies and functional foods. Further research should be investigated to find the in vivo effects of EG005 on gut health and oxidative stress reduction. In addition, attB and attP-based recombination, combined with CRISPR-Cas9 technologies, could offer a more stable alternative for long-term sodA gene expression in commercial and medical applications.